2017
DOI: 10.1007/s00345-017-2084-7
|View full text |Cite
|
Sign up to set email alerts
|

A prospective randomized comparison among SWL, PCNL and RIRS for lower calyceal stones less than 2 cm: a multicenter experience

Abstract: RIRS and PCNL were more effective than SWL to obtain a better SFR and less auxiliary and re-treatment rate in single lower calyceal stone with a CT diameter between 1 and 2 cm. RIRS compared to PCNL offers the best outcome in terms of procedure length, radiation exposure and hospital stay. ISRCTN 55546280.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
79
4
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(91 citation statements)
references
References 34 publications
5
79
4
3
Order By: Relevance
“…It is very well discussed in literature as a systematic review and meta-analysis showed PCNL and RIRS were superior to ESWL in stone clearance and even PCNL is more effective then RIRS(9). In 2017 Bozzini et al performed a prospective randomized comparison among ESWL, PCNL and RIRS on <2cm sized LC stones (10). ESWL was failed against PCNL and RIRS considering SFR and re-treatment rates(p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is very well discussed in literature as a systematic review and meta-analysis showed PCNL and RIRS were superior to ESWL in stone clearance and even PCNL is more effective then RIRS(9). In 2017 Bozzini et al performed a prospective randomized comparison among ESWL, PCNL and RIRS on <2cm sized LC stones (10). ESWL was failed against PCNL and RIRS considering SFR and re-treatment rates(p<0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons believed that either RIRS or PCNL surgery is needed even if the diameter of LPSs is less than 1.0 cm [18]. Endourology surgery is widely used to treat calculi with diameter less than 2.0 cm [19]. The application of RIRS or UMP in the treatment of calculi larger than 2 cm in diameter is rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…Some surgeons believed that either RIRS or PCNL surgery is needed even if the diameter of LPSs is less than 1.0 cm [18]. Endourology surgery is widely used to treat calculi with diameter less than 2.0 cm [19]. The application of RIRS or UMP in the treatment of calculi larger than 2cm in diameter is rarely reported.…”
Section: Discussionmentioning
confidence: 99%